European Society of Biomechanics S.M. Perren Award 2022: Standardized tibio-femoral implant loads and kinematics. (August 2022) - Dreyer, Michael J.; Trepczynski, Adam; Hosseini Nasab, Seyyed Hamed; Kutzner, Ines; Schütz, Pascal; Weisse, Bernhard; Dymke, Jörn; Postolka, Barbara; Moewis, Philippe; Bergmann, Georg; Duda, Georg N.; Taylor, William R.; et al.
Abstract: Knowledge of both tibio-femoral kinematics and kinetics is necessary for fully understanding knee joint biomechanics, guiding implant design and testing, and driving and validating computational models. In 2017, the CAMS-Knee datasets were presented, containing synchronized in vivo implant kinematics measured using a moving fluoroscope and tibio-femoral contact loads measured using instrumented implants from six subjects. However, to date, no representative summary of kinematics and kinetics obtained from measurements at the joint level of the same cohort of subjects exists. In this study, we present the CAMS-Knee standardized subject "Stan", whose reference data include tibio-femoral kinematics and loading scenarios from all six subjects for level and downhill walking, stair descent, squat and sit-to-stand-to-sit. Using the peak-preserving averaging method by Bergmann and co-workers, we derived scenarios for generally high (CAMS-HIGH100), peak, and extreme loading. The CAMS-HIGH100 axial forces reached peaks between 3022 and 3856 N (3.08–3.93 body weight) for the five investigated activities. Anterior-posterior forces were about a factor of ten lower. The axial moment around the tibia was highest for level walking and squatting with peaks of 9.4 Nm and 10.5 Nm acting externally. Internal tibial rotations of up to 8.4° were observed during squat and sitting, while the walking activities showed approximately half the internal rotation. The CAMS-HIGH100 loads were comparable to Bergmann and co-workers', but have the additional benefit of synchronized kinematics. Stan's loads are +11 to +56% higher than the ISO 14243 wear testing standard loads, while the kinematics exhibit markedly different curve shapes. Along with the original CAMS-Knee datasets, Stan's data can be requested at cams-knee.orthoload.com .